2022
DOI: 10.1002/ldr.4238
|View full text |Cite
|
Sign up to set email alerts
|

Assessing local perceptions of deforestation, forest restoration, and the role of agroecology for agroecosystem restoration in northern Malawi

Abstract: Deforestation drives climate change and reinforces food insecurity in forestdependent communities. What drives deforestation varies by location and is shaped by livelihood systems. But how locals perceive restoration is crucial for developing restoration policies. Evidence suggests that applying sustainable farming strategies can potentially restore forests and sustain livelihoods. Applying a broad-based conceptualization of deforestation and restoration in policymaking, however, results in missed opportunitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…Specifically, agroecology improves agricultural productivity and food security, making diverse crops available that can improve dietary diversity and income for smallholder farmers. In addition, agroecology contributes towards the restoration of degraded lands and forestry [66], which improves carbon sequestration. As an alternative to industrial agriculture, agroecological practices such as agroforestry maintain habitats and connectivity for biodiversity and support ecosystem functions under climate stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, agroecology improves agricultural productivity and food security, making diverse crops available that can improve dietary diversity and income for smallholder farmers. In addition, agroecology contributes towards the restoration of degraded lands and forestry [66], which improves carbon sequestration. As an alternative to industrial agriculture, agroecological practices such as agroforestry maintain habitats and connectivity for biodiversity and support ecosystem functions under climate stress.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence points to the fact that agroecology leads to the restoration of farmlands and degraded forests [65,66]. In a study examining the perceptions of deforestation, forest restoration, and the role agroecology, it was found that farmers who practise agroecology reported varied levels of forest restoration after applying agroecological practices on their farms compared to farmers who did not practise agroecology [66].…”
Section: Agroecosystem and Forest Restoration For Carbon Sequestrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some agroecology principles can help to mitigate the impacts of climate change and reduce the risk of future disasters (Kpienbaareh et al, 2022). For example, in regions where prolonged droughts and floods have disrupted traditional agriculture, agroforestry systems that combine crops, trees and livestock have effectively provided diverse and nutritious food sources while restoring degraded landscapes.…”
Section: Ecological Restoration and Recoverymentioning
confidence: 99%
“…The application considered in this paper is bi-temporal deforestation detection in tropical rain forests, e.g. those in the Brazilian Amazon region, which is particularly important because deforestation is one of the major causes of global warming (Kpienbaareh et al, 2022). The goal is to analyse a pair of co-registered satellite images acquired at different points in time in order to predict at pixel level whether deforestation occurred between the two dates or not, which can be seen as a special case of pixel-wise classification.…”
Section: Introductionmentioning
confidence: 99%